Growth, Yield and Quality of Sweet Corn (Zea mays L. Saccharata) as Influenced by Spacing and INM Practices Under South Gujarat Condition - Manishaben, Rathod; Bavalgave, V. G.; Patil, V. A.; Deshmukh, S. P. (International Journal of Economic Plants, 2018)
A field experiment was conducted at college farm, N. M. College of Agriculture, Navsari Agricultural University, Navsari (GJ), during rabi season in 2016–17 to study the influence of of spacing and integrated nutrient management on sweet corn (zea mays L. saccharata) under south Gujarat condition”. The experiment was laid out in Factorial randomized blok design (FRBD) with three replications. The factors consisted of three spacing (45×30 cm2, 60×20 cm2 and 60×30 cm2), three nutrient management practices (100% RDF (120:60:00 NPK kg ha-1, 75% RDF+25% RDN through Biocompost and 50% RDF+50% RDN through Biocompost) and two biofertilizers i.e. with Azotobactor+PSB+KMB and without biofertilizers. The results revealed that, spacing 60×20 cm2 recorded significantly higher green cob (91.93 q ha-1) and fodder yield (318.65 q ha-1) While, Significantly higher protein content in cob (6.97%) and fodder (2.92%) was recorded in spacing 60×30 cm2 (S3). Application of 100% RDF (120:60:00 NPK kg ha-1) recorded the significantly highest green cob (90.13 q ha-1), fodder yield (311.74 q ha-1) and protein content in cob (6.91%) and fodder (2.95%). Biofertlizers i.e. Azotobacter+PSB+KMB application recorded the significantly highest green cob (86.64 q ha-1), fodder yield (299.68 q ha-1) and protein content in cob (6.85%) and fodder (2.85%).